Tinjauan Yuridis Industri E-Commerce dalam Melakukan Kegiatan Transaksi Online - Dewa Gede Ananta Prasetya; Anak Agung Sagung Laksmi Dewi; Ni Made Puspasutari Ujianti (Jurnal Konstruksi Hukum, 2022)
This research is motivated by the development of information technology which is currently changing people's lifestyles. With the internet, it is easier to transact online, especially with online shopping applications. The online trading industry has had a rapid impact with the public shopping culture. The two problems found in this research are how the e-commerce legal arrangements in Indonesia and the legal consequences of not implementing the e-commerce industry in accordance with Law Number 7 of 2014 concerning Trade. The normative research method is a data collection technique in this research, by processing data sourced from the existing legal rules and related legal materials. From the results of this research, it was found that in the applicable law online trading, it is mandatory to hold permits, complete and accurate information for consumers. In this case, it is concluded that the e-commerce industry must pay close attention to legal regulations related to the provision of goods and services, lest consumers suffer losses due to the existence of the e-commerce industry, by sending inappropriate goods. It is likely that consumers will lose.